2022
DOI: 10.3389/fmicb.2021.803862
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Antimicrobial Resistance, Virulence Determinants and Biofilm Formation Ability Among Extraintestinal Pathogenic Escherichia coli Strains Isolated in Catalonia, Spain

Abstract: Escherichia coli is a well-characterized bacterium highly prevalent in the human intestinal tract and the cause of many important infections. The aim of this study was to characterize 376 extraintestinal pathogenic E. coli strains collected from four hospitals in Catalonia (Spain) between 2016 and 2017 in terms of antimicrobial resistance, siderophore production, phylogroup classification, and the presence of selected virulence and antimicrobial resistance genes. In addition, the association between these char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…However, this explanation does not fully account for the increased proteins from the fim operon, indicating the involvement of broader regulatory mechanisms. A recent study has reported a direct correlation between biofilm formation and the colibactin operon in isolates of E. coli and K. pneumoniae 71,72 . Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin 73 , it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway.…”
Section: Discussionmentioning
confidence: 98%
“…However, this explanation does not fully account for the increased proteins from the fim operon, indicating the involvement of broader regulatory mechanisms. A recent study has reported a direct correlation between biofilm formation and the colibactin operon in isolates of E. coli and K. pneumoniae 71,72 . Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin 73 , it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway.…”
Section: Discussionmentioning
confidence: 98%
“…coli and K. pneumoniae. , Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin, it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway. Recently, a phenotypic switch between type III fimbriae and the hypermucoviscous capsule in response to iron levels has been reported in the SGH10 strain. , The iron-regulated outer membrane protein IroP, encoded in the virulence plasmid, inhibits the expression of the mrk operon under low iron conditions, inhibiting biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported a direct correlation between biofilm formation and the colibactin operon in isolates of E. coli and K. pneumoniae. 64,65 Furthermore, since it has been demonstrated that the inactivation of PPK by mutagenesis reduces the promoter activity of clbB (the gene that encodes for an essential enzyme for colistin biosynthesis) and decreases the production level of colibactin, 66 it is possible that the absence of this enzyme also leads to a decrease in biofilm formation through this pathway. Recently, a phenotypic switch between type III fimbriae and the hypermucoviscous capsule in response to iron levels has been reported in the SGH10 strain.…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm formation capacity of the isolates was evaluated using the 96-well microtiter plate assay as previously described [ 17 ]. In short, bacterial suspensions in Luria Bertani (LB) broth were incubated at 37 °C for 18–24 h with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive research on the relationship between antimicrobial resistance and biofilm formation capacity has produced contradictory findings. It was reported that biofilm formation enhances bacterial resistance by several mechanisms, such as reduced antimicrobial diffusion and delayed growth rates [ 13 , 17 ]. Conversely, other studies suggested that antimicrobial resistance bears a considerable fitness cost on bacterial cells, which may reduce their biofilm formation ability.…”
Section: Introductionmentioning
confidence: 99%